2011
DOI: 10.1038/mp.2011.155
|View full text |Cite
|
Sign up to set email alerts
|

QTL replication and targeted association highlight the nerve growth factor gene for nonverbal communication deficits in autism spectrum disorders

Abstract: Autism Spectrum Disorder (ASD) has a heterogeneous etiology that is genetically complex. It is defined by deficits in communication and social skills and the presence of restricted and repetitive behaviors. Genetic analyses of heritable quantitative traits that correlate with ASD may reduce heterogeneity. With this in mind, deficits in nonverbal communication (NVC) were quantified based on items from the Autism Diagnostic Interview Revised. Our previous analysis of 228 families from the Autism Genetics Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Our novel pathway analysis supports previously published data on alterations in pathways in ASD, such as oxidative stress [61], mTOR [38], Natural Killer cells [59,60], NGF, and monocyte pathways [112], as well as activation of microglia (macrophages in the periphery) [22,109]. However, this is the first study to suggest DAS/DEU occurs in these pathways and thus confirmation is needed in a future independent cohort.…”
Section: Discussionsupporting
confidence: 88%
“…Our novel pathway analysis supports previously published data on alterations in pathways in ASD, such as oxidative stress [61], mTOR [38], Natural Killer cells [59,60], NGF, and monocyte pathways [112], as well as activation of microglia (macrophages in the periphery) [22,109]. However, this is the first study to suggest DAS/DEU occurs in these pathways and thus confirmation is needed in a future independent cohort.…”
Section: Discussionsupporting
confidence: 88%
“…However, no common variation has been identified or even reached the threshold of regional significance (correcting for multiple testing based on only those SNPs within the linkage region), perhaps with the exception of CNTNAP2 (contactin associated proteinlike 2) and NGF (nerve growth factor). 23,24 Additionally, no association signals have been found that can account for the linkage peaks in these regions, which suggests that even within segments shared by affected families, rare genetic variation is likely to be playing a significant part, consistent with the expectations of small individual-allele effect sizes from common variants. 25 …”
Section: Gene Discovery In Asdmentioning
confidence: 93%
“…An exonic polymorphism, rs6330, was selected for comparison with previous psychotherapy studies (Lester et al, 2012;Hudson et al, 2013). We selected other six intronic SNPs: rs11102929 (Mercader et al, 2008), rs17033692 (Lu et al, 2013), rs7523654 (Gratacos et al, 2010), rs12760036 (Park et al, 2011), rs6678788 (Cui et al, 2011) in intron 1; and rs2254527 (Toma et al, 2013) in intron 2.…”
Section: Selection Of Genetic Variantsmentioning
confidence: 99%